Dihydrofolate Reductase/Thymidylate Synthase Fine-Tunes the Folate Status and Controls Redox Homeostasis in Plants. Issue 11 (22nd September 2017) - Gorelova, Vera; De Lepeleire, Jolien; Van Daele, Jeroen; Pluim, Dick; Meï, Coline; Cuypers, Ann; Leroux, Olivier; Rébeillé, Fabrice; Schellens, Jan H.M.; Blancquaert, Dieter; Stove, Christophe P.; Van Der Straeten, Dominique
Abstract : The Arabidopsis DHFR-TS (dihydrofolate reductase-thymidylate synthase) isoform THY3 operates as an inhibitor of its family members, thereby regulating folate and NADPH availability in cells. Abstract: Folates (B9 vitamins) are essential cofactors in one-carbon metabolism. Since C1 transfer reactions are involved in synthesis of nucleic acids, proteins, lipids, and other biomolecules, as well as in epigenetic control, folates are vital for all living organisms. This work presents a complete study of a plant DHFR-TS (dihydrofolate reductase-thymidylate synthase) gene family that implements the penultimate step in folate biosynthesis. We demonstrate that one of the DHFR-TS isoforms (DHFR-TS3) operates as an inhibitor of its two homologs, thus regulating DHFR and TS activities and, as a consequence, folate abundance. In addition, a novel function of folate metabolism in plants is proposed, i.e., maintenance of the redox balance by contributing to NADPH production through the reaction catalyzed by methylenetetrahydrofolate dehydrogenase, thus allowing plants to cope with oxidative stress.